Does the auditor have a direct influence on the financial statement quality? - Tatiana Dolgikh (European Financial and Accounting Journal, 2017)
In the modern process of globalization, IFRS standards are widely used in the financial world, Russian Federation is one of these examples. The application of IFRS in Russian Federation first began in the early 90-ies of the twentieth century. During IFRS adoption many companies were involved in this process. Nowadays, a big part of all Russian companies obligatory use IFRS standards to prepare their statements. The purpose of this article is to analyse current practices of financial reporting procedures, its compliance with the rules of the IAS 1 as well as identifying the dependencies between the auditor selection and the quality of reporting. For this paper, a special Questionnaire was developed and for each selected organization a special profile, which included analysis of all financial statements for the period of the 2015 year was created. The study shows that the financial reports quality of the largest Russian companies on a high level. However, many companies face the problem of RAS and IFRS differences during reports transformation that directly influences its quality. During the study process it becomes clear, that auditor has a direct impact on the financial statements quality.
Keywords: M41; M42; 650; IFRS; Quality; Reports; Russian Companies